Efficient Removal of Mercury from Polluted Aqueous Solutions Using the Wireless Bipolar Electrochemistry Technique. Issue 12 (21st December 2022) - Fattah, Zahra Ali
Abstract: Mercury represents one of the major toxic pollutants in water that affect human and ecosystem. Extensive efforts have been globally invested to remove mercury using various chemical and electrochemical approaches. In this study, I propose the use of bipolar electrochemistry for the first time for mercury depollution process. Mercury(II) is removed from aqueous solutions by direct electrodeposition on millimeter scale graphite rods held in a bipolar setup. By adjusting the strength of the applied electric field and the number of the graphite rods the efficiency of the system can be controlled. This wireless technique allows the use of multiple graphite rod arrays within the bulk cell which resulted in high removal efficiency (98 %) of Hg 2+ ions from the polluted solution. The method is straightforward, green, and efficient. The concept can be adapted to remove other heavy metal ions or electrochemically active contaminants from polluted water as long as their reduction potentials are within the water stability window. Abstract : Divalent mercury was efficiently removed from synthetic aqueous samples by electrodeposition on graphite rod arrays in a wireless manner using bipolar electrochemistry. The method is green, simple and highly efficient.